Symmetric surface electromagnetic waves at flat interface plasma –vacuum - Galaydych, V.K.; Galaydych, K.V. (Вопросы атомной науки и техники, 2007)
As it is known the surface electromagnetic waves (SEW) can propagate along surface, which separates two media with the permittivity of different signs . A lot of works devoted to studies and applications of plane SEW. We have shown that new type of SEW can propagate along the boundary of free plasma with vacuum. The equiphase surfaces of these waves are the circular cylinders in contrast to planes in case of conventional surface waves. The properties of these unconventional SEW are presented. The dispersion characteristics, the field distribution and Poynting vector for these waves were obtained. Comparison of properties of conventional and unconventional SEW have been analysed. Відомо, що поверхневі електромагнітні хвилі (ПЕХ), можуть поширюватись уздовж поверхні, що розділяє два середовища з діелектричними сталими різних знаків . Багато робіт присвячено вивченню плоских ПЕХ. Ми показали, що ПЕХ нового типу можуть поширюватись уздовж межі вільної плазми з вакуумом. Еквіфазними поверхнями у цих хвиль є кругові циліндри, а не площини, як у випадку звичних поверхневих хвиль. Отримано дисперсію, розподіл полів та вектор Пойнтинга для цих хвиль. Проведено порівняння властивостей звичайних та вивчених в даній роботі ПЕХ. Известно, что поверхностные электромагнитные волны (ПЭВ), могут распространяться по поверхности, которая разделяет две среды с диэлектрическими постоянными различных знаков . Много работ посвящено изучению плоских ПЭВ. Мы показали, что ПЭВ нового типа могут распространяться по границе свободной плазмы с вакуумом. Эквифазными поверхностями у этих волн есть круговые цилиндры, а не плоскости, как в случае обычных поверхностных волн. Получены дисперсия, распределение полей и вектор Пойнтинга для этих волн. Проведено сравнение свойств обычных и рассмотренных в данной работе ПЭВ.